2023
DOI: 10.3389/fonc.2023.1102269
|View full text |Cite
|
Sign up to set email alerts
|

Dacarbazine-encapsulated solid lipid nanoparticles for skin cancer: physical characterization, stability, in-vivo activity, histopathology, and immunohistochemistry

Abstract: BackgroundThis study examined the use of solid lipid nanoparticles (SLNs) to administer Dacarbazine (DTIC) to skin melanoma cells with minimal adverse effects. Melanoma is a tricky skin cancer to cure, and standard chemotherapy has many negative effects. Encapsulating DTIC in SLNs may allow the drug to target melanoma cells without harming healthy cells. The study developed and tested DTIC-loaded SLNs for skin melanoma treatment.MethodsThis study encapsulated Dacarbazine (DTIC) in solid lipid nanoparticles (SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
3
1
0
Order By: Relevance
“…Similar effects were observed in independent studies in in vitro [119] and in vivo [120] experiments. Mice treated with 5-FU-SNL exhibited decreased inflammatory responses, less keratinization, and reduced signs of angiogenesis when compared to mice treated with 5-FU [120].…”
Section: Solid Lipid Nanoparticlessupporting
confidence: 88%
See 3 more Smart Citations
“…Similar effects were observed in independent studies in in vitro [119] and in vivo [120] experiments. Mice treated with 5-FU-SNL exhibited decreased inflammatory responses, less keratinization, and reduced signs of angiogenesis when compared to mice treated with 5-FU [120].…”
Section: Solid Lipid Nanoparticlessupporting
confidence: 88%
“…The use of SNLs for drug encapsulation resulted in a significant improvement in their anticancer properties, increased drug retention and bioavailability. Histopathological analysis showed that rats treated with decarbazine-SNLs had less keratosis, inflammatory responses, and angiogenesis than rats treated with free dacarbazine [120]. Similar effects were observed in independent studies in in vitro [119] and in vivo [120] experiments.…”
Section: Solid Lipid Nanoparticlessupporting
confidence: 78%
See 2 more Smart Citations